Romantic deliriums: Charles Nodier’s gothic universe - Camarani, Ana Luiza Silva (Lettres Françaises, 2008)
In the short story “Smarra ou les démons de la nui” (1821), Charles Nodier follows the gothic line, one of the forms of the fantastic narrative which emanates from the romantic literature and prolongs the English pre-Romantic tendency, known as gothic novel or roman noir. However Nodier changes this modality of the narrative and his highly complex dreamlike logic announces some proceedings which will be used in contemporary narratives.